Pituitary adenoma treatment plan quality comparison between linear accelerator volumetric modulated arc therapy and Leksell Gamma Knife® radiosurgery - Veselsky, T; Syruckova, T; Kindlova, A; Osmancikova, P (Medical dosimetry, 2021)
The aim of this study was to compare radiosurgical treatment plan quality of a linear accelerator with Leksell Gamma Knife (LGK) for pituitary adenoma irradiation. Thirty pituitary adenoma patients were evaluated in this study. Treatment plans were prepared on LGK and stereotactic linear accelerator Varian TrueBeam STx. Volumetric Modulated Arc Therapy (VMAT) plans (21 plans with 2 coplanar arcs and 9 plans with 4 non-coplanar arcs) were calculated for linear accelerator. All the plans were evaluated in terms of conformity, selectivity, gradient index and organ at risk (OAR) sparing. VMAT produced dosimetrically comparable treatment plans to LGK regarding conformity and selectivity (New Conformity Index (NCI): 1.76 ± 0.65 for 4 arc VMAT, 2.33 ± 1,16 for 2 arc VMAT and 1.96 ± 0.71 for LGK; Selectivity Index (SI): 0.63 ± 0.16 for 4 arc VMAT, 0.51 ± 0.16 for 2 arc VMAT and 0.58 ± 0.17 for LGK). Gradient index (GI) was superior for LGK plans (GI: 2.74 ± 0.20 for LGK and 5.28 ± 2.29 for 4 arc VMAT). OAR sparing for optics, brainstem, and hypophysis was similar for both modalities while target volume coverage was maintained the same. Finally, treatment time resulted in favor of VMAT plans (in this study VMAT plans were almost 5 times faster than LGK treatment regarding beam on time). According to the results of this study stereotactic linear accelerator with VMAT treatment could be used as a reasonable alternative to LGK for pituitary adenoma radiosurgery but only if the same head fixation method accuracy and target volume delineation are maintained for both modalities.
Keywords: celková dávka radioterapie; Pituitary Neoplasms; Radiotherapy, Intensity-Modulated; Radiotherapy Dosage; Radiosurgery; Brain Neoplasms; radioterapie s modulovanou intenzitou; nádory hypofýzy; plánování radioterapie pomocí počítače; lidé; částice - urychlovače; Humans; Particle Accelerators; nádory mozku; radiochirurgie; Radiotherapy Planning, Computer-Assisted